Dissecting the influence of cellular senescence on cell mechanics and extracellular matrix formation in vitro. Issue 3 (13th December 2022) - Brauer, Erik; Lange, Tobias; Keller, Daniela; Görlitz, Sophie; Cho, Simone; Keye, Jacqueline; Gossen, Manfred; Petersen, Ansgar; Kornak, Uwe
Abstract: Tissue formation and healing both require cell proliferation and migration, but also extracellular matrix production and tensioning. In addition to restricting proliferation of damaged cells, increasing evidence suggests that cellular senescence also has distinct modulatory effects during wound healing and fibrosis. Yet, a direct role of senescent cells during tissue formation beyond paracrine signaling remains unknown. We here report how individual modules of the senescence program differentially influence cell mechanics and ECM expression with relevance for tissue formation. We compared DNA damage‐mediated and DNA damage‐independent senescence which was achieved through over‐expression of either p16 Ink4a or p21 Cip1 cyclin‐dependent kinase inhibitors in primary human skin fibroblasts. Cellular senescence modulated focal adhesion size and composition. All senescent cells exhibited increased single cell forces which led to an increase in tissue stiffness and contraction in an in vitro 3D tissue formation model selectively for p16 and p21‐overexpressing cells. The mechanical component was complemented by an altered expression profile of ECM‐related genes including collagens, lysyl oxidases, and MMPs. We found that particularly the lack of collagen and lysyl oxidase expression in the case of DNA damage‐mediated senescence foiled their intrinsic mechanical potential. These observations highlight the active mechanical role of cellular senescence during tissue formation as well as the need to synthesize a functional ECM network capable of transferring and storing cellular forces. Abstract : Cellular senescence modulates single cell mechanics and ECM formation with consequences for macroscopic tissue tensioning. Components of the SASP and a reduced collagen expression as a result of DNA damage‐mediated senescence competes with the increased mechanical potential of these cells.